Saliva tau and phospho-tau-181 measured by Lumipulse in patients with Alzheimer’s disease - Marksteiner, Josef; Defrancesco, Michaela; Humpel, Christian (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a severe neurodegenerative brain disorder. The determination of beta-amyloid (Aβ)-40, –42, total tau, and phospho-tau-181 (pTau181) in cerebrospinal fluid (CSF) using Lumipulse technology has been established as biomarkers for AD in recent years. As CSF collection is an invasive procedure, one aims to find biomarkers in blood or other human fluids, such as saliva. In the present study, we aim to measure these markers in human saliva. Using Salivettes, we collected saliva samples from healthy controls (n = 27), patients with AD dementia (n = 44), mild cognitive impairment (MCI) (n = 45), depression (n = 31), and 21 blinded samples, all older than 60 years. Lumipulse technology with a G600II was used to detect all four biomarkers. Our data show that the levels of total protein were highly variable and thus biomarker levels were corrected to 1 mg/ml of total protein. Saliva Aβ−40 and –42 were not detectable, because it was not recovered from the Salivettes. However, saliva total tau (577 ± 134 pg/mg, n = 22) and phospho-tau-181 (9.7 ± 1.3 pg/mg, n = 21) could be analyzed by Lumipulse technology. Saliva total tau levels were significantly decreased in patients with AD (≤ 300 pg/mg protein), while pTau181 levels (≥ 18 pg/mg protein) were significantly enhanced in patients with MCI compared to controls. Laboratory diagnosis with a cut-off of ≥ 18 pg/mg protein pTau181 (for MCI) and ≤ 300 pg/mg protein tau (for AD) for blinded samples could diagnose MCI and AD with an accuracy of 71.4%. Despite these initial promising results, the findings must be replicated in larger cohorts, and several technical problems due to saliva processing must be solved and Salivettes should not be used.